ALGORITMA C45 UNTUK MENENTUKAN MAHASISWA PENERIMA BEASISWA (STUDI KASUS : PPS IAIN RADEN INTAN BANDAR LAMPUNG) - Rahman, Muhammad Arif (244-5567)
Academic achievement of students evaluated each semester to determine learning outcomes. If the student can meet certain academic criteria to be declared worthy of continued study of the student passed the course. The high number of students in college can be maximized by Scholarship. Therefore, the number of participants who submitted many scholarships, as well as indicators of the many criteria, a system is needed that can help to determine who is entitled to receive a scholarship from the college.In this research, formulated by research question, as namely applying C.45 algorithm, which aims to select the candidates in Post Graduate Program IAIN Raden Intan Lampung to obtained the scholarship recipients with a high degree of accurance. The methodology used by the authors to determine the candidates in the Post Graduate Program IAIN Raden Intan Lampung using Algorithm stages C.45, the classification process of grantees using the five steps in the KDD (Knowledge Discovery in Databases), which includes several activities, namely selection, preprocess, transformation, data mining, interpretation and evaluation.The sample of the research are 40 (forty students) awardees at the Graduate Program IAIN Raden Intan Lampung and has been produced based on the calculation algorithm C.45 total of 18 (eighteen) students who do not deserve to be recipients for having a GPA <3.00, then as many as eight (8) students who do not deserve to be recipients because they have tenure <5 years and noncivil service workers, to produce as many as fourteen (14) students who deserve to be recipients forhaving met the criteria for scholarship recipients darisegi GPA, work and tenure predetermined.Keywords: Algorithm C.45, Scholarship